Pengaruh Keterampilan Psikomotor Terhadap Kemampuan Memahami Materi Suhu dan Kalor pada Siswa X IA-1 SMA Negeri 8 Banda Aceh - Nurrizayani Nurrizayani (JURNAL FISIKA EDUKASI, 2014)
The aim of this study was to determine whether there is any effect on the ability of psychomotor students understand the substansi temperature and the heat of the students, describe the activities of teachers and students in learning activities , to determine the ability of teachers to manage teaching and learning activities specific to the skills practice psychomotor grade students X IA - 8 SMA Negeri 1 Banda Aceh . The subjects were students of class X IA - 8 SMA Negeri 1 Banda Aceh as many as 30 students . The instrument used in this study is a written test and observation sheets . Based on the results of data processing of the data concluded that: (1) there is influence between students' mastery of the psychomotor domain of student achievement in physics classes XIA-1 SMA Negeri 8 Banda Aceh temperature and heat content . In other words , the higher the value of psychomotor a student, the higher the student achievement in the subjects of physics, (2) learning the psychomotor domain practice was able to reduce the tendency for the teacher to dominate the learning activities through lectures, and able to bring students to dominate learning activities. The most dominant role of the teacher is to guide students to conduct experiments ( 24.81 % ) , and ( 3 ) learning melatihkan psychomotor domains can increase student activity, the most prominent student activity is conducted experiments (26.88%).